Experimental evaluation of VF controlled Off-grid generating system - Gupta S.K.; Srivastava R.K. (My University, 2025)
Off-grid generating system suffers problems of voltage and frequency (VF) fluctuation as per the variable input wind/hydro/solar power. The problem has been discussed and to regulate VF of a wind based off-grid system a special dual-stator axial flux permanent magnet generator has been designed. Experimental evaluation of the generator has been performed and presented in the paper. © 2016 IEEE.